2019
DOI: 10.2298/abs190122019t
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pregnancy-specific β-1-glycoprotein on the helper T-cell response

Abstract: Pregnancy-specific β-1-glycoproteins (PSGs) are capable of regulating innate and adaptive immunity. As fetal antigens circulate in the blood of pregnant women, it is of particular interest to reveal the effects of PSGs on the differentiation of memory T cells in the context of maternal-fetal tolerance formation. We studied if, native PSG preparation affects helper T-cell proliferation, the frequencies of CD4 + CD45R0 + , CD4 + CD45RA + , CD4 + CD45RA + CD45R0 + cells, naive CD45RA + CD45R0-CD62L + cells (NAIVE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Our previous study showed the general inhibitory effect of PSG on the proliferation of helper T cells (CD4 + ) under conditions of Th17-polarization [13]. In addition, we also found that PSG inhibits the proliferation of T helpers in the presence of IL-2 while preventing the conversion of naïve T cells into a terminally differentiated effector T -helpers [12]. Considering that PSG affected cells via activation of the latent form of TGF-β1 [4], we suggest that TGF-β1-mediated antiproliferative effects of PSG are versatile for all lymphocytes.…”
Section: Resultsmentioning
confidence: 59%
“…Our previous study showed the general inhibitory effect of PSG on the proliferation of helper T cells (CD4 + ) under conditions of Th17-polarization [13]. In addition, we also found that PSG inhibits the proliferation of T helpers in the presence of IL-2 while preventing the conversion of naïve T cells into a terminally differentiated effector T -helpers [12]. Considering that PSG affected cells via activation of the latent form of TGF-β1 [4], we suggest that TGF-β1-mediated antiproliferative effects of PSG are versatile for all lymphocytes.…”
Section: Resultsmentioning
confidence: 59%
“…The cells form fairly distinct populations that can be gated, and you can calculate what percentage of the total number of cells ends up in each gate. This method was previously described in our article [71], and in a subsequent article [72], we showed that the percentage of proliferating cells obtained by differential gating correlated with the percentage of Ki67 + cells.…”
Section: Flow Cytometrymentioning
confidence: 70%
“…On the FSC/SSC plot, cells were first gated (cell debris was excluded), and then gates of non-proliferating, proliferating, and apoptotic cells were selected in the cell gate ( Figure 4 ). Then, the percentage of cells falling into each of these gates was determined from the total number of cells [ 26 , 27 ]. Data were collected using a CytoFLEX S flow cytometer and analyzed using CytExpert software (Beckman Coulter, Brea, CA, USA).…”
Section: Methodsmentioning
confidence: 99%